2016
DOI: 10.1055/s-0036-1584299
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Infectious Complications in Gastroschisis on Costs and Length of Stay

Abstract: Outcomes for gastroschisis (GS) remain highly variable and avoiding infectious complications (ICs) may represent a significant improvement opportunity. Our objective was to provide estimates of the impact of IC on length of stay (LOS) and costs. Using a national database, 1,378 patients with GS were identified. Patient and hospital characteristics were compared and LOS and costs evaluated for patients with and without IC. Two-thirds of all GS patients had IC, and IC were common for simple and complex GS (65, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…reported that two-thirds of all GS patients had ICs, and hospital LOS in patients with ICs was significantly longer in patients without infection [16]. They found that 65% of simple GS patients and 73% of complex GS patients had ICs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that two-thirds of all GS patients had ICs, and hospital LOS in patients with ICs was significantly longer in patients without infection [16]. They found that 65% of simple GS patients and 73% of complex GS patients had ICs.…”
Section: Discussionmentioning
confidence: 99%
“…Neonates with GS are at a greater risk of nosocomial and opportunistic infections because of their comorbidities and immunological status. These patients often require additional surgical interventions, prolonged time to achieve full enteral feeding, and have extended hospital LOS [16]. Infectious complications (ICs) such as wound infections and sepsis, have been demonstrated to affect outcomes, including hospital LOS and mortality [17].…”
Section: Discussionmentioning
confidence: 99%
“…In surgical patients, infections are frequent complications and, therefore, a reason of concern 16 . Even with the improvement in neonatal intensive care, sepsis is still among the main causes of neonatal morbidity and mortality, associated with longer hospital stays and hospital costs 12,[16][17][18] . Neonatal sepsis, in addition to being a risk for delayed motor development, is associated with the incidence of cerebral palsy and high mortality 16,18 .…”
Section: Discussionmentioning
confidence: 99%
“…An observational and retrospective study was carried out, comprising 17 Maternal, neonatal, surgical data, duration of ventilatory support, length of stay, main complications and morbidities, motor assessment data by TIMP, and patient outcome through electronic medical records were collected, creating a database in the Microsoft program ® Excel (2013) for data tabulation.…”
Section: Methodsmentioning
confidence: 99%
“…1 Second, complications are associated with an increase in hospital stay and costs. 2,3 Third, complications are frustrating and stressful events for the surgeon, 4 may cause anxiety, loss of confidence, and reduced job satisfaction. 5 Prevention and timely and correct management are key factors in dealing with complications.…”
mentioning
confidence: 99%